2013
DOI: 10.1111/imm.12047
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐γ‐ and glucocorticoid‐mediated pathways synergize to enhance death of CD4+ CD8+ thymocytes during Salmonella enterica serovar Typhimurium infection

Abstract: SummaryThymic atrophy is known to occur during infections; however, there is limited understanding of its causes and of the cross-talk between different pathways. This study investigates mechanisms involved in thymic atrophy during a model of oral infection by Salmonella enterica serovar Typhimurium (S. typhimurium).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(91 citation statements)
references
References 60 publications
5
85
0
1
Order By: Relevance
“…5a). IFN-c was shown to participate in the induction of thymic atrophy and T-cell depletion during viral and bacterial infections, such as severe influenza A(H1N1)pdm09, Salmonella enteric serovar Typhimurium, and Mycobacterium avium (Borges et al, 2012;Deobagkar-Lele et al, 2013;Liu et al, 2014). We showed directly that IFN-c increased the apoptosis of thymocytes using an in vitro culture experiment (Fig.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…5a). IFN-c was shown to participate in the induction of thymic atrophy and T-cell depletion during viral and bacterial infections, such as severe influenza A(H1N1)pdm09, Salmonella enteric serovar Typhimurium, and Mycobacterium avium (Borges et al, 2012;Deobagkar-Lele et al, 2013;Liu et al, 2014). We showed directly that IFN-c increased the apoptosis of thymocytes using an in vitro culture experiment (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…versus mock-infected). IFN-c is a key cytokine involved in the protective immune response against various pathogen infections (Flynn et al, 1993;Julkunen et al, 2001), but has also been shown to participate in the induction of pathological courses, especially thymic atrophy and T-cell depletion during viral or bacterial infections (Borges et al, 2012;Deobagkar-Lele et al, 2013;Liu et al, 2014).…”
Section: Nk-cells Were Activated By Influenza Virus Infectionmentioning
confidence: 99%
“…Other inflammatory mediators may rise during infection, leading to thymic damage, and again in particular depletion of the DP population. These include tumour necrosis factor α, the release of which can be triggered by infection with Francisella tularenis (46) and Trypanosoma cruzi infection (47); as well as the release of interferon γ caused by Salmonella enterica infection (48). …”
Section: Causes and Targets Of Acute Thymic Damagementioning
confidence: 99%
“…Furthermore, inhibition of the endogenous corticosteroid signaling partially reversed the atrophy of the thymus whereas enhancement of endogenous host-encoded IFN-γ participated in the apoptosis of the DP thymocytes. Moreover, interactions between these two key pathways led to an additive effect on the reduction in the DP thymocyte survival (Deobagkar-Lele et al 2013). More recently, a skewed process of thymocyte development was detected during S. typhimurium-induced ATI as a primary event that caused continuous development of thymocytes leading to a set of SP thymocyte clones that exhibited a unique T cell receptor β chain (TCR-Vβ), which was independent of the changes in thymic architecture during the course of the infection.…”
Section: Bacterial Infections and Atimentioning
confidence: 99%